(untitled) (Journal of Engineering, 2011)
Flow of water under concrete dams generates uplift pressure under the dam, which may cause the dam to function improperly, in addition to the exit gradient that may cause piping if exceeded a safe value. Cutoff walls usually used to minimize the effect of flow under dams. It is required to 1)minimize the flow quantity to conserve water in the reservoir, it is also required to 2)minimize the uplift pressure under the dam to maintain stability of the dam, and it is required to 3) minimize the exit gradient to prevent quick condition to occur at the toe of the dam where piping may occur and may cause erosion of the soil. Varying the angle of cutoff walls affects its influence on the factors aforementioned that are required to be minimized. In this paper, the cutoff wall angle was varied from 0° to 180° using GeoStudio 2007 SEEP/W computer program, and the variations of the three factors were studied and analyzed. The results shows that the best angle to minimize the water flow is about 60°, the best angle to minimize the uplift pressure was about 120° to 135°, and the best angle to minimize the exit gradient was about 45° to 75°. The case where two cutoff walls were used one with angle 60°, the other with an angle 120° were investigated. The results indicated where the minimum values for all factors may be obtained.